Attitudes and self‐efficacy towards adults with mild intellectual disability among staff in acute psychiatric wards: an empirical investigation. Issue 2 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to investigate whether acute inpatient psychiatric staffs' attitudes and self‐efficacy towards adults with mild intellectual disability, were different than towards the general mental health population. And whether their understanding of the policy for those with mental illness and intellectual disability differed.Design/methodology/approach – The study is a between‐subject design, using a self‐administered postal questionnaire. The sample was all qualified staff from the acute inpatient psychiatric provision of an inner London borough. Potential participants were randomly assigned to two research groups, half being given a questionnaire regarding people with intellectual disability and the other half an identical one regarding people with mental illness. Comparisons were made between the two.Findings – The majority of staff were unaware of the current policy direction for adults with intellectual disability although were on the whole in agreement to the idea that they should access mainstream services. Staff overall did not have more negative attitudes to those with intellectual disability although were less likely to empower or encourage self‐advocacy. Staff were significantly less confident that they had sufficient training and experience, and in their perceived ability to be able to communicate, assess and treat adults with mild intellectual disability when compared to those with mental illness.Research limitations/implications – The response rate and small sample size is a limitation. Further research could usefully look at whether self‐efficacy and attitudes differ in different models of mainstream psychiatric care.Originality/value – Government policy in the UK regarding services for people with intellectual disability advocates for inclusion and equality (Chaplin and Taggart, 2012). Those requiring psychiatric care should access this from mainstream services (Department of Health, 2001, 2009, 2011; Foundation for People with Learning Disabilities et al., 2004; Bradley, 2009.) There are, however, no UK‐based studies investigating the views of mainstream acute inpatient psychiatric staff towards their role. Intellectual disability staff have concerns about their attitudes and self‐efficacy and it is know that acute care is the setting where most adults with intellectual disability will come across mainstream psychiatric staff. Findings have relevance to managers and staff in both intellectual disability and psychiatric services and could be considered in the context of trying to work together as is the direction of policy.